How methamphetamine exposure during different neurodevelopmental stages affects social behavior of adult rats? - Hrebíčková, Ivana; Ševčíková, Mária; Macúchová, Eva; Šlamberová, Romana (Physiology & behavior, 2017)
Social behavior involves complex of different forms of interactions between individuals that is essential for healthy mental and physical development throughout lifespan. Psychostimulants, including methamphetamine (MA), have neurotoxic effect, especially, if they are targeting CNS during its critical periods of development. The present study was aimed on evaluation of changes in social interactions (SI) following scheduled prenatal/neonatal MA treatment in combination with acute application in adulthood. Eight groups of male and eight groups of female rats were tested in adulthood: rats, whose mothers were exposed to MA (5mg/ml/kg) or saline (SA, 1ml/kg) during the first half of gestation (ED 1-11), the second half of gestation (ED 12-22) and neonatal period (PD 1-11). To do this, we compared indirect neonatal applications via the exposed dams with group of rat pups that received MA or SA directly through injections. In adulthood, half animals from each group were injected with MA (1mg/kg), second half with saline 45min prior to the Social Interaction Test. Females and males were observed for social and nonsocial activities of two unfamiliar individuals of the same sex and treatment in a familiar Open field arena. The present study demonstrated that prenatal/neonatal MA exposure leads to decrease the time spent in genital investigation, following and nonsocial activity. Acute dose of MA leads to a decrease in all SI patterns and to an increase in nonsocial activities relative to acute SA. Females were more active than males. Animals exposed to prenatal/neonatal treatment during the second half of gestation (ED 12-22) and throughout lactation period (PD 1-11 indirect/direct) had fewer SI and greater exploratory behavior than animals exposed during the first half of gestation (ED 1-11).
Keywords: Social Behavior; modely nemocí na zvířatech; Prenatal Exposure Delayed Effects; Animals, Newborn; Male; Rats, Wistar; Sex differences; Sex Characteristics; zpožděný efekt prenatální expozice; náhodné rozdělení; estrální cyklus; Pregnancy; těhotenství; mužské pohlaví; Estrous Cycle; pohlavní dimorfismus; potkani Wistar; Trimesters; novorozená zvířata; Central Nervous System Stimulants; methamfetamin; Animals; stimulanty centrálního nervového systému; Methamphetamine; ženské pohlaví; zvířata; pohybová aktivita; Disease Models, Animal; Motor Activity; Random Allocation; Social interaction; sociální chování; Female